2016
DOI: 10.1016/j.ccell.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

N-Myc Drives Neuroendocrine Prostate Cancer Initiated from Human Prostate Epithelial Cells

Abstract: SUMMARY MYCN amplification and overexpression are common in neuroendocrine prostate cancer (NEPC). However, the impact of aberrant N-Myc expression in prostate tumorigenesis and the cellular origin of NEPC have not been established. We define N-Myc and activated AKT1 as oncogenic components sufficient to transform human prostate epithelial cells to prostate adenocarcinoma and NEPC with phenotypic and molecular features of aggressive, late-stage human disease. We directly show that prostate adenocarcinoma and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
327
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 304 publications
(359 citation statements)
references
References 46 publications
(78 reference statements)
14
327
0
Order By: Relevance
“…Importantly, FZD4 was upregulated upon T/E overexpression, and inhibition of FZD4 led to reduced phosphorylation of p38. These results confirmed reports that loss of cell adhesion and EMT are associated with FZD4-induced activation of WNT signaling [49].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Importantly, FZD4 was upregulated upon T/E overexpression, and inhibition of FZD4 led to reduced phosphorylation of p38. These results confirmed reports that loss of cell adhesion and EMT are associated with FZD4-induced activation of WNT signaling [49].…”
Section: Discussionsupporting
confidence: 81%
“…Histone modifications play an important role in chromatin organization and transcriptional modulation indicating a link between histone modification and differential DNA methylation, which is supported in many recent studies [49,50]. This further suggested that dysregulation of histone modifying genes could lead to an altered DNA methylation in T/E expressing cells.…”
Section: Microarray Profiling Indicates Differentially Expressed Epigsupporting
confidence: 58%
See 3 more Smart Citations